2015
DOI: 10.1007/s00229-015-0790-2
|View full text |Cite
|
Sign up to set email alerts
|

Positive isotropic curvature and self-duality in dimension 4

Abstract: We study a positivity condition for the curvature of oriented Riemannian 4-manifolds: The half-P IC condition. It is a slight weakening of the positive isotropic curvature (P IC) condition introduced by M. Micallef and J. Moore.We observe that the half-P IC condition is preserved by the Ricci flow and satisfies a maximality property among all Ricci flow invariant positivity conditions on the curvature of oriented 4-manifolds.We also study some geometric and topological aspects of half-P IC manifolds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…For Einstein manifolds with PIC, Brendle [4] proved that they must be isometric to the round sphere S n , up to scaling. Later, in dimension n = 4, this result was extended by Richard-Seshadri [46], in which they showed that a compact oriented Einstein 4-manifold with half PIC is isometric to S 4 or CP 2 . On the other hand, for gradient shrinking Ricci solitons, it was proved recently by Li-Ni-Wang [31] that any 4-dimensional complete gradient shrinking Ricci soliton with PIC is a finite quotient of either S 4 or S 3 × R.…”
Section: Introductionmentioning
confidence: 91%
“…For Einstein manifolds with PIC, Brendle [4] proved that they must be isometric to the round sphere S n , up to scaling. Later, in dimension n = 4, this result was extended by Richard-Seshadri [46], in which they showed that a compact oriented Einstein 4-manifold with half PIC is isometric to S 4 or CP 2 . On the other hand, for gradient shrinking Ricci solitons, it was proved recently by Li-Ni-Wang [31] that any 4-dimensional complete gradient shrinking Ricci soliton with PIC is a finite quotient of either S 4 or S 3 × R.…”
Section: Introductionmentioning
confidence: 91%
“…In [RS13b], H. Seshadri and the author used the results from [RS13a] to prove that the cones C IC + and C IC − enjoy some kind of maximality among oriented Ricci flow invariant nonnegative curvature cones in dimension 4.…”
Section: The Case Of Dimensionmentioning
confidence: 99%
“…Richard and Seshadri [14], Fine, Krasnov, and Panov [5], and the author [19] proved that if the metric has half nonnegative isotropic curvature, then it is either half conformally flat or Kähler. LeBrun [8] proved that if W + (ω, ω) > 0 for some ω ∈ H 2 + (M ), then the metric is Hermitian.…”
Section: Introductionmentioning
confidence: 99%